Deep electroacupuncture of neurogenic spots attenuates immobilization stress-induced acute hypertension in rats - Cong Zhan; Han Byeol Jang; DanBi Ahn; Suchan Chang; Yeonhee Ryu; Hyung Kyu Kim; Bong Hyo Lee; Xiaowei Guan; Yu Fan; Bae Hwan Lee; Hee Young Kim (Integrative Medicine Research)
Background: Our previous studies proved that neurogenic inflammatory spots (or neurogenic spots) have the same physiological features as acupuncture points and that neurogenic spot stimulation generates therapeutic effects in various animal models. However, it is unclear how deeply the neurogenic spots should be stimulated to generate therapeutic effects. Methods: The effects of acupuncture at various needle depths below the neurogenic spot were examined in a rat immobilization stress-induced hypertension (IMH) model. Electroacupuncture was applied to a neurogenic spot at depths of 1, 2, or 3 mm using a concentric bipolar electrode. Results: Electrical stimulation of the neurogenic spot at a 3-mm depth most effectively lowered blood pressure compared with controls and stimulation at 1- and 2-mm depths, which was inhibited by pretreatment with a local anesthetic lidocaine. Electrical stimulation of the neurogenic spot or injection of substance P (SP) at a 3-mm depth significantly excited the rostral ventrolateral medulla (rVLM) compared with superficial stimulation. Electrical stimulation applied at a 3-mm depth on neurogenic spots dominantly caused c-fos expression from rVLM and ventrolateral periaqueductal gray (vlPAG) in IMH rats. Pretreatment with resiniferatoxin (RTX) injection into the neurogenic spot to ablate SP or calcitonin gene-related peptide (CGRP) prevented the effects of 3-mm neurogenic spot stimulation on blood pressure in IMH rats. Conversely, artificial injection of SP or CGRP generated anti-hypertensive effects in IMH rats. Conclusion: Our data suggest that neurogenic spot stimulation at a 3-mm depth generated anti-hypertensive effects through the local release of SP and CGRP and activation of rVLM and vlPAG.